Computer aided-dynamic navigation technology for efficient single visit endodontic treatment of pulp canal obliteration: A case report - Varma, K Madhu; Dasari, Lokesh; Mavidi, Jagapathi Babu; Mantena, Satyanarayana Raju; Dalavai, Praveen; Ajjimera, Katyayani (International Journal of Dental Materials, 2025)
Dental trauma causes a variety of issues and perplexes practitioners. One of the consequences of trauma is pulp canal obliteration (PCO), which presents a challenge in treatment due to the high likelihood of procedural errors and complications. To overcome these challenges, Guided endodontics was introduced using personalised 3D guides by overlaying DICOM and STL files (Static navigation) or real-time navigation (Dynamic navigation) of the patient. A dynamic navigation system (DNS) is a computer‑aided navigation technology analogous to the Global Positioning System (GPS) navigation. Dynamic navigation provides real-time, precise guidance using 3D imaging, helping practitioners accurately navigate and treat calcified canals by visualising and accessing challenging areas without damaging tooth structure. The current case report describes the management of pulp canal obliteration using the dynamic navigation system in a single visit. A 30-year-old female complained of pain in the upper front teeth region for the past two months, with a history of trauma 10 years ago. The clinical examination revealed no caries, cracks, or discolouration. Tooth 12 was sensitive to percussion. Pulp sensibility tests were negative. On radiographic examination, the pulp canal was partially obliterated until the middle third. Tooth 12 was diagnosed as necrotic pulp with symptomatic apical periodontitis. After reviewing options, the case was root canal treated using a dynamic navigation system. A successful negotiation of the canal was done followed by completion of root canal treatment. The patient was asymptomatic with intact periapical structures at the 1-year follow-up period. Computer-aided dynamic navigation proved to be safe, fast, and predictable for negotiating calcified canals with minimal risk of errors in a single visit.